2011
DOI: 10.1038/nature10443
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tet3 DNA dioxygenase in epigenetic reprogramming by oocytes

Abstract: Sperm and eggs carry distinctive epigenetic modifications that are adjusted by reprogramming after fertilization. The paternal genome in a zygote undergoes active DNA demethylation before the first mitosis. The biological significance and mechanisms of this paternal epigenome remodelling have remained unclear. Here we report that, within mouse zygotes, oxidation of 5-methylcytosine (5mC) occurs on the paternal genome, changing 5mC into 5-hydroxymethylcytosine (5hmC). Furthermore, we demonstrate that the dioxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
935
10
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,006 publications
(1,024 citation statements)
references
References 35 publications
54
935
10
11
Order By: Relevance
“…The paternal genome in the male pronucleus undergoes rapid demethylation after fertilization, with DNA methylation being largely lost before the first mitosis. This active demethylation is mediated by Tet3, a dioxygenase that converts 5-methlycytosine to 5-hydroxymethlycytosine and which is present specifically in the male pronucleus [19]. By contrast, the maternal genome in the female pronucleus remains highly methylated until cleavage stages, when methylation is passively lost over the entire genome.…”
Section: Epigenetic Asymmetries Between Maternal and Paternal Genomesmentioning
confidence: 99%
“…The paternal genome in the male pronucleus undergoes rapid demethylation after fertilization, with DNA methylation being largely lost before the first mitosis. This active demethylation is mediated by Tet3, a dioxygenase that converts 5-methlycytosine to 5-hydroxymethlycytosine and which is present specifically in the male pronucleus [19]. By contrast, the maternal genome in the female pronucleus remains highly methylated until cleavage stages, when methylation is passively lost over the entire genome.…”
Section: Epigenetic Asymmetries Between Maternal and Paternal Genomesmentioning
confidence: 99%
“…Furthermore, a study of the DNA methylation pattern in human 3PN zygotes established that active demethylation of the paternal PN occurs post-fertilization in both c-IVF and ICSI [32]. In addition, recent studies have shown that the demethylation of paternal PN is induced by conversion from 5mC to 5hmC by ten-eleven translocation methylcytosine dioxygenases (TETs) [9][10][11]. Among TET proteins, TET3 is intensely expressed in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that 5-methylcytosine (5mC) in the paternal genome is specifically converted to 5-hydroxymethylcytosine (5hmC) during the pronuclear stage [9][10][11]. Although these three studies were conducted in animals, we applied a similar approach in this study, using epigenetic divergence to determine the origin of mPN and fPN in abnormal human zygotes with 1PN and 3PN.…”
Section: Introductionmentioning
confidence: 99%
“…Chez ces souris, la reprogrammation épigénétique du génome paternel est altérée. Les femelles dont l'allèle maternel est déficient pour Tet3 (Tet3 mat-/pat + ) ont une fécon-dité réduite, et leurs descendants décèdent avec des anomalies dans de multiples organes [23]. Il en est de même pour les souris double KO Tet1 -/-Tet2 -/-dont plus de la moitié meurent en période périnatale de troubles développementaux sévères.…”
Section: Fonctions Biologiques Dans L'embryogenèse Et La Reprogrammatunclassified